Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.1172/jci109691
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Streptozotocin-induced Diabetes Mellitus on Cyclic Nucleotide Regulation of Skeletal Muscle Amino Acid Metabolism in the Rat

Abstract: A B S T R A C T The imllpatet of clial)etes on cyclic nucleotide-associated meclhanismiis regulating skeletal muscle proteini and aminio acid metal)olism was assessed using epitrochlaris preparations fromi streptozotocin-induced diabetic rats. 1 nl epinephrine inhibited alanine and glutamine release from control preparations,lbult no inhibition wvas observed from diabetic preparations with <0.1 mM. 10 nNI epinephrinie stimulated lactate productioni from control muscle but stimulation in diabetic preparattions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 35 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…In a previous study, we found a decreased responsiveness of the catecholamine-sensitive adenylyl cyclase in skeletal muscle obtained from rats with streptozotocininduced diabetes mellitus (10). The results of this study show clearly that streptozotocin-induced diabetes mellitus decreases the responsiveness of glucagon-sensitive adenylyl cyclase in rat liver.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In a previous study, we found a decreased responsiveness of the catecholamine-sensitive adenylyl cyclase in skeletal muscle obtained from rats with streptozotocininduced diabetes mellitus (10). The results of this study show clearly that streptozotocin-induced diabetes mellitus decreases the responsiveness of glucagon-sensitive adenylyl cyclase in rat liver.…”
Section: Discussionsupporting
confidence: 68%
“…Glucagon-stimulable adenylyl cyclase activity has been assessed in liver of animals having a variety of models of diabetes mellitus and has been conflictingly reported to be increased (5)(6)(7), decreased (1,8,9), or unchanged compared with nondiabetic control animals (2). Disparate changes have also been reported for hormone-stimulable adenylyl cyclase activities in other tissues (10)(11)(12)(13)(14). Hormone-stimulable adenylyl cyclase is formed ofthree major components which include: a specific hormone receptor, a catalytic component which catalyzes the reaction forming cAMP from ATP, and a regulatory or coupling system which is comprised ofat least two proteins linking the hormone-receptor complexes to the catalytic component (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that diabetic group exhibited significant decrease in serum total proteins, albumin and globulin along with non-significant change in albumin/globulin ratio (A/G ratio). This might be attributed to several reasons like increased gluconeogenesis and increased rate of amino acid conversion to glucose (62), decreased amino acid uptake (63), disturbance of amino acid levels (64), increased hepatocyte transport membrane (65) increased conversion rate of glycogenic amino acids to CO 2 and H 2 O (66). Also, may be due to the structural distortion and the functional impairment of the hepatic cells which associated with low serum protein and albumin levels (67).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have shown that cyclic nucleotide associated agonists regulate muscle protein degradation and alanine and glutamine synthesis and release. For example, #2-adrenergic agonists, acting through a specific hormone stimulable adenylyl cyclase and increased intracellular levels of cyclic AMP retard muscle protein degradation and thereby inhibit alanine and glutamine synthesis and release (34,35). Similarly, serotonin acting through a specific sarcolemmal D-serotonergic receptor and a hormone stimulable adenylyl cyclase also increases muscle cAMP levels and thereby inhibits protein degradation and alanine and glutamine synthesis and release (21,35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, #2-adrenergic agonists, acting through a specific hormone stimulable adenylyl cyclase and increased intracellular levels of cyclic AMP retard muscle protein degradation and thereby inhibit alanine and glutamine synthesis and release (34,35). Similarly, serotonin acting through a specific sarcolemmal D-serotonergic receptor and a hormone stimulable adenylyl cyclase also increases muscle cAMP levels and thereby inhibits protein degradation and alanine and glutamine synthesis and release (21,35). On the other hand, cholinergic agonists acting through a nicotinic cholinergic receptor increase muscle cGMP levels and as a result increase muscle protein degradation and the formation and release of alanine and glutamine (22,36).…”
Section: Discussionmentioning
confidence: 99%